The Risk of Dependence of Students of Social Media on the Example of Facebook - Wojciech Marcin Czerski; Edyta Gonciarz (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
This paper is devoted to the issue of behavioral addictions associated with social media. The first part describes the phenomenon which social media. They explained the notion of addiction and behavioral addictions for example Facebook. The second part presents the results of the survey, which aim was to diagnose the risk of dependence on Facebook. The presented results showing that only a few of which may be dependent on this medium.